Causes of women׳s postpartum depression symptoms: Men׳s and women׳s perceptions. Issue 7 (July 2015) - Habel, Catherine; Feeley, Nancy; Hayton, Barbara; Bell, Linda; Zelkowitz, Phyllis
Abstract Objectives To describe men's and women's perceptions of the causes of women's PPD symptoms and to explore similarities and differences between men's and women's perceptions. Design Qualitative-descriptive study involving in-depth semi-structured individual interviews and content analysis. Setting In-home interviews of participants recruited in two tertiary care hospitals, both in urban centres of the province of Quebec, Canada. Participants Both members of 30 heterosexual couples from which women scored at least 12 on the Edinburgh Postnatal Depression Scale. Findings Participants described nine causes underlying women's depressive symptoms: societal expectations and pressure on women, physical health problems, transition to parenthood, social connectedness, personality and past psychological history, child health and temperament challenges, unmet care needs, unmet expectations for childbirth, and other life stressors. With one exception, all causes were endorsed by both men and women. Only men mentioned societal pressure on women. Key conclusions and implications for practice Men and women mainly perceived similar causes, which could be explained by socio-cultural factors and extended paternal leaves. Understanding men's and women's perceptions could help tailoring health- care professionals' interventions to couples' needs.